Peran Guru Dalam Meningkatkan Motivasi Belajar Peserta Didik Di SMP Sains Tebuireng Jombang - Muniro, Siti Miftakhul; Hosna, Rofiatul (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2024)
Learning involves the interaction between teachers and female students, where students are given the opportunity to acquire knowledge and skills that shape their attitudes. The research aims to describe the role of teachers in enhancing the motivation to learn of female students at SMP Sains Tebuireng Jombang. This research was conducted at SMP Sains Tebuireng Jombang. The research method used is qualitative, and the data used in this research is primary data. Primary data is data obtained by the researcher through interviews. The sources of data in this research are the school principal, teachers, and students. The data collection techniques are done through observation and interviews. The data analysis techniques include data reduction, data display, and data verification/conclusion. The results of the research show that the role of teachers is to provide knowledge, skills, and guidance to students, as well as to enhance motivation to learn and improve the enthusiasm and learning outcomes of female students. Motivation to learn can be built through stimulation, interest, understanding of the subject matter, and adequate assessment. There are supporting and inhibiting factors in the motivation to learn of female students. One of the supporting factors is behavior, desire, stimulation, affection, capability, and reinforcement. On the other hand, inhibiting factors include differences in the level of understanding among students, lack of interest in the subject matter, lack of motivational encouragement from parents, and feelings of inadequacy in competing.